2006
DOI: 10.1016/j.eurpsy.2005.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric side effects induced by supraphysiological doses of combinations of anabolic steroids correlate to the severity of abuse

Abstract: ObjectiveThe objective of our study was to evaluate the psychological consequences of real-world AAS use in athletes abusing such agents, in comparison with a placebo and control group of comparable athletes, while correlating the severity of abuse with the side effects observed. The hypothesis tested by the study was that the use of AAS induces a wide range of psychological side effects whose impact and emergence is dependent upon the severity of the abuse.DesignThe study includes a substantial group of AAS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 62 publications
0
94
1
1
Order By: Relevance
“…The long-term consequences for the physiology and mental health of individuals combining AAS with all these agents are not easy to foresee. There are a number of reports available in the literature showing that polysubstance use combined with AAS at high doses can result in severe complications [3,8,12,40,41] . The adverse effects of the drugs taken, the interactions associated with polypharmacy, the effects of the large dosages and the increased risk of addiction to other drugs of abuse and alcohol are all major health care concerns that require further study.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term consequences for the physiology and mental health of individuals combining AAS with all these agents are not easy to foresee. There are a number of reports available in the literature showing that polysubstance use combined with AAS at high doses can result in severe complications [3,8,12,40,41] . The adverse effects of the drugs taken, the interactions associated with polypharmacy, the effects of the large dosages and the increased risk of addiction to other drugs of abuse and alcohol are all major health care concerns that require further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, subgroups of steroid abusers may have known psychiatric pre-morbidities that are likely to introduce bias into the suggested causal relationship between anabolic steroid abuse and neuropsychiatric effects. Studies have also shown a correlation between mental side effects and the severity of steroid abuse [14]. The neural systems underlying the aggression induced by AAS appear to overlap with the brain circuits responsible for the regulation of aggression by endogenous androgens such as vasopressin [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in contrast to current prevalences, lifetime prevalence estimates cannot be validated against objective measures such as urine testing (Pagonis et al, 2006). Although subject to the limitations noted above, our prevalence estimates suggest that non-medical AAS use should be considered a major public health problem in the Nordic countries and must require the attention of policy makers and researchers.…”
Section: Discussionmentioning
confidence: 81%